Maternal HBeAg positivity and viremia associated with umbilical cord blood hepatitis B viremia - Le Ye Lee; Guan Huei Lee; Citra Mattar; Sharon Saw; Marion Aw (Pediatrics and Neonatology)
Background: Hepatitis B (HBV) transmission may result from in utero transmission. We aimed to determine the correlation between maternal serum and umbilical cord blood HBV DNA levels in infants delivered by chronic HBV-infected mothers and to describe the effect of cord blood viremia on vertical transmission. Methods: A prospective cohort of 92 chronic HBV-infected mother-and-child pairs recruited over three years was analyzed. Maternal and cord blood were tested for HBV DNA by real-time PCR. Standard immunoprophylaxis with both active and passive immunization was administered to all infants. Serological testing was performed on all infants at 9 months of age. Results: Moderate positive correlation of the maternal HBV DNA with cord blood HBV DNA was demonstrated (r2 = 0.521, p = <0.001). HBeAg +ve mothers were younger with higher HBV and cord viremia. At 9 months of age, one infant was infected. Infants delivered by HBeAg positive mothers and mothers with high HBV DNA of more than 6 LOG IU/mL (1 x 106 IU/mL) have increased relative risk of cord blood viremia. Conclusions: Maternal HBV DNA and presence of HBeAg were positively correlated to cord blood HBV DNA in infants delivered by chronic HBV-infected mothers. Our data suggest that reducing maternal viremia during the antenatal period may help to reduce cord blood viremia. Key Words: cord blood hepatitis B viral (HBV) DNA, hepatitis B core antibody, in-utero exposure to HBV, maternal hepatitis B viral (HBV) DNA